2018
DOI: 10.1007/s12275-018-7510-z
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of 3-acetylbenzamide produced by actinomycete WA23-4-4 from the intestinal tract of Periplaneta americana

Abstract: Actinomycetes are well-known for producing numerous bioactive secondary metabolites. In this study, primary screening by antifungal activity assay found one actinomycete strain WA23-4-4 isolated from the intestinal tract of Periplaneta americana that exhibited broad spectrum antifungal activity. 16S rDNA gene analysis of strain WA23-4-4 revealed close similarity to Streptomyces nogalater (AB045886) with 86.6% sequence similarity. Strain WA23-4-4 was considered as a novel Streptomyces and the 16s rDNA sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…An increasing number of active compounds related to the therapeutic effects of P. americana have been identified in recent years, and at least four active molecules isolated from ‘Xinmailong’ were found to be related to antithrombosis ( Qi et al, 2017 ). In addition, multiple active components from P. americana have been identified as potential drug candidates for wound healing and anti-fungal therapy ( Yun et al, 2017 ; Fang et al, 2018 ; Zhu et al, 2018 ; Yan et al, 2019 ). D-glucosamine and its salts, which are obtained from cockroaches, are employed in dietary supplement products, which have demonstrated positive effects on the treatment of osteoarthritis, knee, and back pain and has an important role in the formation of joints, sinews, bones, heart valves, and respiratory tract ( Bertuzzi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of active compounds related to the therapeutic effects of P. americana have been identified in recent years, and at least four active molecules isolated from ‘Xinmailong’ were found to be related to antithrombosis ( Qi et al, 2017 ). In addition, multiple active components from P. americana have been identified as potential drug candidates for wound healing and anti-fungal therapy ( Yun et al, 2017 ; Fang et al, 2018 ; Zhu et al, 2018 ; Yan et al, 2019 ). D-glucosamine and its salts, which are obtained from cockroaches, are employed in dietary supplement products, which have demonstrated positive effects on the treatment of osteoarthritis, knee, and back pain and has an important role in the formation of joints, sinews, bones, heart valves, and respiratory tract ( Bertuzzi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found that P. americana gut-dwelling bacteria generate anti-bacterial chemicals that may be a source of new anti-bacterial compounds [ [17] , [18] , [19] , [20] ]. The current investigation aimed to determine if secondary metabolites generated by Gordonia , isolated from the gut of P. americana , have any anti-fungal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the existing research reports of insect microorganisms, most of them focus on pest control, biological agents, ecological protection and ecological diversity, and the study on antimicrobial activity of their secondary metabolites is less (Dantur et al 2015 ; Guo et al 2017 ; Zheng et al 2020 ). Our previous study showed that the endobacteria in the intestinal tract of Periplaneta americana exhibited various antimicrobial activities against all tested pathogens (Fang et al 2018 ; Chen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%